2017
DOI: 10.3892/mco.2017.1185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ki-67 assessment in the distribution of breast cancer subtypes: Evaluation in a cohort of Latin American patients

Abstract: Breast cancer (BC) is a heterogeneous disease composed of four main subtypes with distinct clinical and epidemiological features. Although several reports have described the distribution of BC subtypes in Latin America, the majority of them have not included the cellular marker, Ki-67, in the immunohistochemical (IHC) panel. The aim of the present study was to describe the distribution of BC subtypes in a cohort of Latin American women using an IHC panel with Ki-67. A prospective cohort of 580 patients in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…Analisando o perfil imuno-histoquímico dos casos apresentados, o mais prevalente foi o Luminal A conforme dados encontrados na literatura (22,30,33) . Porém o triplo negativo se apresentou mais prevalente do que o Luminal B (30,33) , divergindo do nosso estudo onde o Luminal B aparece mais prevalente que o triplo negativo corroborando com o trabalho de Yábar et al (2017) (34) .…”
Section: Discussionunclassified
“…Analisando o perfil imuno-histoquímico dos casos apresentados, o mais prevalente foi o Luminal A conforme dados encontrados na literatura (22,30,33) . Porém o triplo negativo se apresentou mais prevalente do que o Luminal B (30,33) , divergindo do nosso estudo onde o Luminal B aparece mais prevalente que o triplo negativo corroborando com o trabalho de Yábar et al (2017) (34) .…”
Section: Discussionunclassified
“…Another distinctive feature of BC presentation in LATAM is that young women comprise a large proportion of diagnosed cases. In addition, there is a higher prevalence of triple-negative BC (≈20%) compared with other regions of the world, which leads to the larger burden of aggressive tumours [66, 70].…”
Section: Introductionmentioning
confidence: 99%
“…One typical feature of LATAM patients is a high prevalence of triple-negative breast cancer (up to 21.3%) in contrast to Caucasian populations (around 9%) [82, 86]. Subtypes identification is performed mainly by IHC in the clinical routine.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity seen in luminal tumours could be attributed to the difficulty to discriminate luminal A from luminal B cases, where Ki-67 staining plays a major role. Yabar et al [86] evaluating a mixed cohort of patients from Peru and Uruguay, found that distribution of luminal A tumours change from 41.1% to 31.9% after the inclusion of Ki-67 in the IHC panel to determine the breast cancer subtypes. Inclusion of Ki-67 in the IHC panel to evaluate recently diagnosed breast tumours is relatively new and therefore in the coming years, reports about the distribution of breast cancer subtypes in LATAM will be more accurate and less heterogeneous.…”
Section: Introductionmentioning
confidence: 99%